(untitled) (International Journal of Engineering and Computer Science, 2020)
In this article, we look at recent developments in the Bangladesh garment industry on the issue of efficiency and productivity. First, we were looking for new ideas. How are companies trying to improve their efficiency? Then, we were trying to see if there was a relationship between a companies’ (x) efficiency and cost-saving (a) and increased revenue (y). Of course, intuitively, we would all hypothesise that there must be some relationship between efficiency and reduction of cost of manufacturing and ultimately increased revenue. Further, we would all probably hypothesise that the slope of the function describing that relationship must be significantly higher than zero. Nevertheless, we tried to document the connection so that companies can believe it and give it more attention. Theoretical relationships are one of the weakest ways to try to persuade CEOs of the existence of anything. Show them the numbers, only then they will agree. This paper is an attempt to persuade a readymade garments manufacturing unit to increase efficiency to cut cost and increase revenue, we show that there is a direct causal relation to efficiency and revenue earnings.